2010
DOI: 10.1088/0741-3335/52/12/124015
|View full text |Cite
|
Sign up to set email alerts
|

Non-linear dynamics and plasma flows in a basic toroidal plasma experiment

Abstract: Analyses of non-linear interactions in drift-wave turbulence were carried out in wavenumber space on experimental data obtained from multi-probe measurements in the toroidally confined plasma of the stellarator TJ-K. Recent results are reported. The inverse cascade of energy from small to large scales as typical for two-dimensional turbulence is verified. The transfer in k space is found to be governed by non-local processes. The same way, large-scale zonal flows (ZFs) are found to tap energy from small-scale … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
6
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 37 publications
(58 reference statements)
5
6
0
Order By: Relevance
“…As already found in investigations of the energy transfer between ZF and driftwave turbulence [7,8,32], the predator-prey cycle is also observed here between total turbulent transport Γ tot (t) and ZFs Φ z (t). This is illustrated in Fig.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…As already found in investigations of the energy transfer between ZF and driftwave turbulence [7,8,32], the predator-prey cycle is also observed here between total turbulent transport Γ tot (t) and ZFs Φ z (t). This is illustrated in Fig.…”
supporting
confidence: 85%
“…Due to the twodimensional nature of plasma turbulence in the plane perpendicular to the magnetic field of toroidally confined plasmas, the energetics obey an inverse cascade [2]. Consequently, the ZFs are supposed to gain energy from small-scale drift-wave turbulence by a self-organizing process which was described theoretically [3], observed in nonlinear turbulence simulations [4,5,6], and investigated experimentally in detail [7,8,9,10,11]. It was shown that the flux surface average of the radial derivative of the Reynolds stress ṽ rṽθ is the driving term for ZFs, and that the energy is transferred non-locally in k-space, i.e.…”
mentioning
confidence: 99%
“…via the eddy tilting mechanism. The impact of sheared flows on edge turbulent structures show results that are consistent with the picture of the shear stretching blobs as well as ordering, thus providing a possible explanation for the experimentally observed link between mean sheared flows and the development of LRCs [23,[26][27][28]. In addition, the zonal flow enstrophy and the enstrophy of driftwave turbulence show a phase delay about π/2 [29,30], which is an expected feature of a predator-prey oscillation [10][11][12][13].…”
Section: R/a Psupporting
confidence: 75%
“…Langmuir probes can be used for measuring density and temperature profiles and for direct investigation of plasma turbulence [7,8]. A monopole antenna is used to acquire frequency spectra around 2.45 GHz.…”
Section: Diagnosticsmentioning
confidence: 99%